A legal analysis of fraud vitiating consent in sexual assault cases - Mohamad Yunus, Mohamad Ismail (Bar Council, 2003)
According to Stephen J. in R v Clarence, it is incorrect if the proposition 'fraud vitiates consent' is to be taken in its general understanding and applied without any limitation. He also said that many seductions would be considered as rapes, and so might acts of prostitution produced by fraud. This illustration appears to show clearly that the maxim 'fraud vitiates consent' is too general to be applied in the above situation even though it is absolutely true. Thus, to what extent does 'fraud vitiates consent' apply to sexual intercourse?